(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
Hodgkin lymphoma is a neoplasm arising from lymphoid tissue with distinct morphological and immunohistochemical features. This type of tumor has a characteristic clinical and morphological feature that is inseparable from the treatment of lymphomas, leading to morphological changes. The presence of Reed-Sternberg cells and immunophenotypes are the main criteria for differentiating HL from other lymphoproliferative disorders.